Le vie chirurgiche di accesso: il pilone tibiale - Zottola, V.; Cremona, M.; Bonelli, C.; Foti, A.; Consonni, O. (Lo Scalpello - Journal, 2018)
SURGICAL APPROACHES: TIBIAL PILONTibial pilon fractures represent a noteworthy surgical challenge. Usually caused by high-energy injuries, they are oftenburdened by frequent complications, in particular concerning soft-tissue healing. The literature reports severalsurgical approaches, some fracture-specific, others more extensile, to allow for an easier reduction and fixation of thewhole articular surface. Thus, an accurate preoperative planning and a skilled surgeon play a primary role in themanagement of these injuries.